PENGARUH DIFFERENSIASI PRODUK DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PADA PT PAREWA AERO CATERING MEDAN - vivi Kosalim; Thomas Sumarsan Goh; Errie Margery (JURNAL BISNIS KOLEGA, 2019)
Abstract. This research was conducted at PT Parewa Aero Catering Medan. Buying interest has decreased, as seen from Himodo's food sales due to the negligence of company officers in providing catering orders resulting in disappointment for consumers and catering food delivery times are also limited. The management of the company presents two types of traditional products that are useful to attract the attention of airline logging, but the dishes that are served often occur imperfections and result in airlines complaining about this dish such as the taste of food is not right, the color of the cuisine is less attractive and frequent forgetfulness put chili The taste of chillies put in the order is less spicy so consumers complain. The image of PT Parewa Aero Catering Medan's catering food brand namely Himudo and Himudo is still less well known among customers, so the demand for catering food is not as many as competing companies such as Aerofood ACS Garuda Indonesia catering services. The population in this study were 145 consumers and a sample of 107 consumers. Data collection techniques are by distributing questionnaires, interviews, documentation studies and literature studies. Data analysis using validity and reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. Conclusions in the study that simultaneously product differentiation influences and brand image on consumer buying interest at PT. Parewa Aero Catering Medan. Partially Product Differentiation has an effect on Consumer Buying Interest at PT. Parewa Aero Catering Medan. Partially Brand Image influences Consumer Purchasing Interests at PT Parewa Aero Catering Medan.Â Keywords: Differentiation, Brand Image, Buying InterestÂ